Platinum preparations in the treatment of trophoblastic tumors - I. V. Markina; B. O. Toloknov; L. V. Manzyuk; E. E. Makhova; N. G. Kormosh (Опухоли женской репродуктивной системы)
The N.N. Blokhin Russian Cancer Research Center, Russian Academy of Medical Sciences, has developed and used new polychemotherapy regimens including platinum preparations for the treatment of patients with trophoblastic tumors. A cysplatin + ethoposide or carboplatin + ethoposide (CyE/CaE) combination was used as second-line chemotherapy in methotrexate-resistant locally advanced form (Stages I-II) of the disease. A cysplatin or carboplatin + methotrexate + dactinomycin + vincristine) (CyMDV/CaMDV) regimen was used as first-line therapy in patients with disseminated (Stage III-IV) disease and as second-line therapy in patients with its resistant form (Stages III-IV). The CyE/CaE regimen could cure 21 patients with Stages I-II without surgical intervention. When the CyMDV/CaMDV regimen was used as first-line therapy in 24 patients with Stages III-IV disease, of them 21 (87.5%) patients achieved a complete therapeutic effect, they all have been survivors to the present time. The CyMDV/CaMDV regimen used as second-line chemotherapy in patients with the resistant form turned out to be effective in 5 (83.3%) of 6 cases. The follow-up lasted > 3 years.The benefit of the developed regimens including platinum preparations is that they are effective, less toxic, require long hospitalization and are technically simpler, which allows them to be used in the outpatient setting of the wide oncological network.